Tackling strong biofilm and multi-virulent vancomycin-resistant Staphylococcus aureus via natural alkaloid-based porous nanoparticles: perspective towards near future eradication - Abd El-Hamid, Marwa I.; Ibrahim, Doaa; Elazab, Sara T.; Gad, Wafaa M.; Shalaby, Marwa; El-Neshwy, Wafaa M.; Alshahrani, Mohammed Abdulrahman; Saif, Ahmed; Algendy, Reem M.; AlHarbi, Maha; Saleh, Fayez M.; Alharthi, Afaf; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
As a growing direction, nano-based therapy has become a successful paradigm used to address the phytogenic delivery-related problems in overcoming multivirulent vancomycin-resistant Staphylococcus aureus (VRSA) infection. Hence, our aim was to develop a novel nanocarrier system (mesoporous silica nanoparticles, MPS-NPs) for free berberine (Free-BR) as an antimicrobial alkaloid against strong biofilm-producing and multi-virulent VRSA strains. Our outcomes demonstrated vancomycin resistance in 13.7% of Staphylococcus aureus (S. aureus) strains categorized as VRSA. Notably, strong biofilm formation was observed in 69.2% of VRSA strains that were all positive for the icaA gene. All strong biofilm-producing VRSA strains harbored a minimum of two virulence genes comprising clfA and icaA with 44.4% of them possessing all five virulence genes (icaA, tst, clfA, hla, and pvl), and 88.9% were multi-virulent. The study findings affirmed excellent in vitro antimicrobial and antibiofilm properties of BR-loaded MPS-NPs. Real-time quantitative reverse transcription PCR (qRT-PCR) assay displayed the downregulating role of BR-loaded MPS-NPs on strong biofilm-producing and multi-virulent VRSA strain virulence and agr genes in both in vitro and in vivo mice models. Additionally, BR-loaded MPS-NPs supplementation has a promising role in attenuating the upregulated expression of pro-inflammatory cytokines' genes in VRSA-infected mice with attenuation in pro-apoptotic gene expression resulting in reduced VRSA-induced apoptosis. In essence, the current study recommends the future scope of using BR-loaded MPS-NPs as auspicious alternatives for antimicrobials with tremendous antimicrobial, antibiofilm, anti-quorum sensing (QS), and anti-virulence effectiveness against problematic strong biofilm-producing and multi-virulent VRSA-associated infections.